Destination Image: Tourists' perspective versus residents' perspective - Agapito, Dora (2014)
The study of destination image has been asserting itself as an instrument of differentiation, helping to increase the destinations competitiveness. Despite being a well-documented topic in the literature, there had been a lack of studies to compare the perspectives of tourists with the residents. The main objective of this study is to measure the image of Lagos in the Algarve region, the most important Portuguese destination, comparing the perspectives of tourists and residents in a cognitive, affective and behavioral approach. The empirical investigation included a mixed methodology. First, in an exploratory phase, the analysis of open-ended questions allowed to detect the attributes for the analysis of the cognitive component, enabling a holistic approach. Then, the use of questionnaires to a sample of 379 tourists and 378 residents provided a quantitative methodology, using descriptive indicators, hypotheses tests and the multivariate CHAID technique. Results indicate a positive global destination image in the perspective of both stakeholders. The attributes more consensually associated with Lagos are the „good weather‟ and „good beaches‟, although these variables have not significant discriminatory power for the dependent variable „recommendation of the destination to friends and family‟, in the CHAID analysis. Thus, in the tourists‟ perspective, the „interesting cultural heritage‟ is the most significant explanatory variable, while for the residents this is translated into „good value for money‟. In the emotional approach, both stakeholders associate the destination to the adjectives “arousing/exciting/pleasant”.